Estimating Sectoral Energy Demand in Pakistan - Khan, Raza Ali; Ahmed, Mirza Faizan; Ghoor, Jaweriya Naz (iRASD Journal of Economics, 2023)
The energy sector is fuel for the development of the economy as it affects multiple sectors. Consideration of socio-economic impact, it is essential to plan for sustainable energy. For optimal energy usage, it is important to identify demand and supply in Pakistan along with existing challenges. This research aims to estimate Pakistan's energy demand for all five sectors: industrial, residential, transportation, commercial, and agriculture. Different factors have been recognized and analyzed for this research aim that influence the energy demand in each sector. This study Applied box Jenkins which followed systematic procedures including identification, estimate, analytical check, and forecasting of the model. This approach is relevant for the medium- and long-term time series data. The results indicate that the final energy demand is affected by different factors among which the main factor is the applied tariff in that sector and the real GDP of Pakistan. Consumption of each source of energy varies in each sector. From the overall analysis, it has been found that the major share of energy is from transportation oil which accounts for 27.5%, followed by a second share of 12.9% of industrial gas at 12.9%, domestic gas at 12.0%, and industrial coal at 20.4%. From the analysis of the results, the core issue in the energy sector is a gap in energy demand-supply in Pakistan due to a deficit of oil and gas and import dependency. Compared to the previous year's result it has been found that there is an increase in each sector with higher growth in industrial, residential and commercial demand. Price and real GDP were effective in determining the demand for energy sources in each sector. Based on the results, it is recommended to minimize dependency on imported energy sources and promote innovative and sustainable energy production.